Trade talks: Where is the development? - Michael Fleshman (Africa Renewal, 2006)
It was a close thing. But after six days of arm-twisting, all-night bargaining sessions and closed-door meetings in Hong Kong, an eleventh-hour concession by Europe on farm subsidies saved the December 2005 summit meeting of the World Trade Organization (WTO) from another embarrassing collapse. The European move kept the troubled global trade liberalization talks, launched at Doha, Qatar, in 2001, alive — but just barely. UK Trade Minister Alan Johnson described the agreement reached in Hong Kong as only “one step up from failure.” Even WTO Director-General Pascal Lamy, who praised the 13–18 December summit for bringing the talks “out of hibernation,” conceded that negotiators were barely past the halfway point a year after the round was supposed to be finished.